Basic Microbiology: Instructions on Laboratory Exercises - Primec, Maša; Langerholc, Tomaž (2017)
Bridging the gap between the theoretical and the practical application of what students are learning is the first step towards understanding the central roles of microorganisms in nature and in our daily lives. Our goal for these instructions on laboratory exercises is to provide a bridge that helps our foreign students, who choose the Microbiology course (Erasmus exchange program), to integrate lectures with laboratory experience.
Keywords: Basic Microbiology; Instructions; Laboratory exercises; Microbiology course; Students